Effect of fennel seed powder ( Foniculum Vulgare) on antioxidant enzymes and histlogical of small intestin ( jujenum) of broiler chickens. - zain, DR .Doaa zain; Measem H. Alallawee; zain, Moaed H.sayhood (University of Thi-Qar Journal of agricultural research, 2024)
This research was investigate the effects of Foeniculum Vulgare (F.V) powder on antioxidant enzyams, , height of the villus to the depth of the villi in the jejunum region of grill chicks. A sum of 144 one-day old chicks (Ross 308)were used in the experiment and randomly distributed into twelve cages ( 12 birds / cage). It was contained four treatments (T1: regular feed without any addition, T2: regular feed supplemented with 10 gm of F.V powder / kg of ration, T3: regular feed with 15 gm of F.V powder/kg of ration and T4: regular feed with 20 gm of F.V powder/kg of ration. Results showed The effect of F.Vulgare adding on the activity of some liver enzymes in the blood serum of broilers that there are significant differences (P<0.05) between the treatments. as it showed a significant increase in the activity enzyme ( SOD ,GPX). The effectiveness of malondihyde acid (MDA) in blood serum was measured, as the results of the table show that there is a significant decrease (P<0.05) in the effectiveness of acid (MDA) in blood serum for the addition treatments .And the villus height, villus depth, and the ratio of villus height to villus depth in the jejunum of broilers indicates a highly significant superiority (P<0.05) in villus height, villus depth, and the ratio between villus height to villus depth for the jejunum area for the treatments to which fennel was added compared to the treatment .